Incidence of Oral Candidiasis in Patients with Asthma Using Inhaled Corticosteroids by Various Inhaler Devices - Saeed Ahmad, Sana Iqbal, Mubeenun Nisa, Shamshad Ali, Shariq Ali Khan, Usman Ashfaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study was to do the comparison of the incidence of oral candidiasis in individuals with inhaled corticosteroids by Rota caps via Revolizer and metered dose inhalers via spacer. Place and Duration: This Cross-sectional study was held in the Pulmonology department of Gulab Devi Hospital, Lahore for six-months duration from March 2021 to August 2021. Methods: Patients with asthma who were referred to chest clinics and used MDI inhaled corticosteroid with spacer or Rota cap with Revolizer for minimum two-months were alienated into 2 groups. The A Group included patients using metered dose inhalers with spacer and inhaled steroids and group B patients using Rota cps with Revolizer. The treating physician examined all patients for oropharyngeal candidiasis, and a thorough throat examination in patients was done who reported dysphonia or throat ache. Results: Of 120 patients (group A: 60 and group B: 60) who participated in the analysis, 72 (60%) were female and 48 (40%) were male. Their ages fluctuated from 15 to 75 (mean 43.2). 89 patients (74.2%) were encompassed in the analysis with moderate asthma and severe asthma was noted in 31 patients (25.8%). 39 patients (32.5%) described throat ache; 81 patients (67.5%) did not have such symptoms. The oral candidiasis incidence was noted in 18 (15%) in group B patients who used Rotacaps encompassing 6mcg and Formeterol Fumerate 400 mcg Budesonide and 12 (10%) in group A patients using MDI containing Salmeterol xinafoate 25 and Fluticasone propionate 250 mcg with spacer device. It was advanced in B group patients than A group (p <0.05). The oral candidiasis incidence in individuals over 50 years was also higher than patients under 50 years. Conclusion: This analysis exhibited a high proportion of oral candidiasis among individuals using Rota caps containing formoterol and Budesonide by Revolizer in comparison to metered dose inhalers with spacer.